2020
DOI: 10.1111/cpr.12763
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between tubular epithelial cells and glomerular endothelial cells in diabetic kidney disease

Abstract: In recent years, although the development of clinical therapy for diabetic kidney disease (DKD) has made great progress, the progression of DKD still cannot be controlled. Therefore, further study of the pathogenesis of DKD and improvements in DKD treatment are crucial for prognosis. Traditional studies have shown that podocyte injury plays an important role in this process. Recently, it has been found that glomerulotubular balance and tubuloglomerular feedback (TGF) may be involved in the progression of DKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 47 publications
1
56
0
5
Order By: Relevance
“…27 In line with these reports, we found that involved in the pathology of DKD. 31,32 Thus, future studies designed to determine whether complement activation also affects other renal cell types and to elucidate the crosstalk between these cells during DKD are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In line with these reports, we found that involved in the pathology of DKD. 31,32 Thus, future studies designed to determine whether complement activation also affects other renal cell types and to elucidate the crosstalk between these cells during DKD are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hyperactivation of complement C5 may contribute to the development and progression of diabetic glomerulosclerosis in T2DM. However, other types of renal cells, such as podocytes and tubular epithelial cells, are also involved in the pathology of DKD 31,32 . Thus, future studies designed to determine whether complement activation also affects other renal cell types and to elucidate the crosstalk between these cells during DKD are needed.…”
Section: Discussionmentioning
confidence: 99%
“…These cells, in intimate contact with blood, are more sensitive to changes in circulatory conditions. 25…”
Section: Discussionmentioning
confidence: 99%
“…DKD is associated with endothelial dysfunction (Chen et al, 2020). Endothelial GLP-1R has been shown to be involved in endothelial dysfunction in a mouse angiotensin II-induced hypertension model (Helmstadter et al, 2020).…”
Section: The Endothelial Functionmentioning
confidence: 99%